2021
DOI: 10.1111/btp.13053
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filtering and deforestation shape frog assemblages in Amazonia: An empirical approach assessing species abundances and functional traits

Abstract: Biological assemblages are often predictable from knowledge of natural environmental heterogeneity and change in response to anthropogenic disturbances, such as deforestation, so understanding ecological mechanisms and processes mediating assemblages is essential to direct conservation actions. We sampled frogs along an edaphic and vegetation-structure gradient in the Brazilian Amazon to test the hypothesis that assemblages change in species composition and functional trait characteristics across landscapes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Habitat components, as such water availability, soil granulometry and vegetation structure, modulate the distribution of many taxa in tropical landscapes (Oliveira et al, 2009; Peixoto et al, 2023; Rabelo et al, 2021; Torralvo et al, 2021). Particularly for aquatic insects, these factors may be associated with the distinct habitats, such as phytotelmata, ponds and streams, which are used by the immature stages of many species (Gray, 1981; Nakanishi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat components, as such water availability, soil granulometry and vegetation structure, modulate the distribution of many taxa in tropical landscapes (Oliveira et al, 2009; Peixoto et al, 2023; Rabelo et al, 2021; Torralvo et al, 2021). Particularly for aquatic insects, these factors may be associated with the distinct habitats, such as phytotelmata, ponds and streams, which are used by the immature stages of many species (Gray, 1981; Nakanishi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some populations of this species group from central Amazonia and the Guiana Shield have been historically identified as P. ockendeni (Boulenger, 1912)-a species described based on three syntypes from La Union, Huacamayo River, Carabaya, Departamento Puno, southeastern Peru, at about 800 m above sea level (a.s.l.). Pristimantis ockendeni has been subsequently reported from Brazil, Colombia, Ecuador, Guyana, Suriname (Zimmerman and Rodrigues 1990;Lima et al 2006;Lima et al 2012;Ocampo et al 2016; Silva-e-Silva and Costa-Campos 2018; Azevedo et al 2021;Torralvo et al 2021;Fouquet et al 2022b) and Bolivia (Padial et al 2004;Elmer and Cannatella 2008;Ocampo et al 2016;Frost 2022). However, the identification of these populations as P. ockendeni and, thus, the wide geographic distribution of the species, has been considered doubtful by Elmer et al (2007aElmer et al ( , 2007b, who suggested the existence of undescribed species erroneously associated with this taxon.…”
Section: Introductionmentioning
confidence: 99%